Fenfluramine for seizures associated with Sunflower syndrome. (3rd July 2021) - Geenen, Kennedy R; Doshi, Samarth P; Patel, Sandip; Sourbron, Jo; Falk, Amy; Morgan, Amy; Vu, Uyen; Bruno, Patricia L; Thiele, Elizabeth A
Abstract : Aim: To determine the efficacy of fenfluramine on seizure frequency in patients with Sunflower syndrome. Secondary endpoints were changes in electroencephalogram (EEG) characteristics, cognitive functioning, executive functioning, and quality of life. Method: In this open‐label study, patients underwent a 4‐week baseline period, followed by 3 months of treatment. An oral solution of fenfluramine was administered twice daily for 3 months. The dose was titrated up to a maximum dose of 0.7mg/kg/day or 26mg/day. Cardiac safety was monitored by transthoracic echocardiogram and electrocardiogram. EEGs, abbreviated neuropsychological testing, and questionnaires were administered before starting the study medication and again at the end of the treatment period. Results: Ten patients (eight females, two males; mean age 13y 4mo [SD 4y 11mo], range 7–24y) were enrolled in the study. Nine of the 10 patients completed the core study, eight of whom met the primary endpoint. There were no observations of cardiac valvulopathy or pulmonary hypertension during the study. Interpretation: Treatment with low‐dose fenfluramine resulted in a clinically significant reduction in seizure frequency, including hand‐waving episodes. Fenfluramine may be an effective treatment option for patients with Sunflower syndrome. What this paper adds Nine patients with Sunflower syndrome were treated with fenfluramine. Eight patients were responders, displaying a ≥30% reduction in seizure activity. Six patients experienced a ≥70% reduction in hand‐waving episodes. Improvements on electroencephalogram were observed after treatment with fenfluramine. None of the patients developed evidence of cardiac valvulopathy or pulmonary hypertension. What this paper adds: Nine patients with Sunflower syndrome were treated with fenfluramine. Eight patients were responders, displaying a ≥30% reduction in seizure activity. Six patients experienced a ≥70% reduction in hand‐waving episodes. Improvements on electroencephalogram were observed after treatment with fenfluramine. None of the patients developed evidence of cardiac valvulopathy or pulmonary hypertension.